Changes in driver glance behavior when using a system that automates steering to perform a low-speed parallel parking maneuver. (October 2018) - Kidd, David G.; Reimer, Bryan; Dobres, Jonathan; Mehler, Bruce
Highlights: Automation changed the way drivers allocated attention when parallel parking. Drivers glanced towards the parking space less when steering was automated. Glances were redirected to the instrument cluster showing system information. Drivers also looked at the instrument cluster while approaching a spot. Abstract: Drivers adapt their glance behavior when using automation, which may detract attention from their surroundings. Glance behavior during parallel parking maneuvers performed with and without automated steering was compared. Drivers directed a smaller proportion of their glances toward the parking space and spent less time looking at it when using automation than when not using automation. The proportion of glances and time spent looking at the instrument cluster containing information from the automation increased significantly. Drivers also spent a significantly larger proportion of time looking at the instrument cluster and a smaller proportion looking forward and rearward when using automation while approaching a parking space. The system selected the parking space in the approach phase, which may have drawn attention to the instrument cluster. In conclusion, when using automated steering during parallel parking drivers monitored their surroundings less and looked at system displays more presumably to supervise the automation. The safety implications of these changes in glance behavior should be explored in future research.